دراسة تحليلية للحالات الأولى لتصوير الطرق الصفراوية بالطريق الراجع والأمواج فوق الصوتية ( خبرة مشفى الأسد الجامعي ) خلال العام الدراسي 2006-2007 - ناصر, فيصل; زيزفون, حسان; حمدان, وضاح (Latakia University Journal -Medical Sciences Series, 2019)
شملت هذه الدراسة 105 مريض قبلوا في قسم الداخلية في المشفى. كان الهدف من الدراسة إجراء مقارنة بين نتائج التصوير بالأمواج فوق الصوتية عبر الجلد والتصوير الراجع للطرق الصفراوية ERCP داخل وخارج الكبد . فالإيكو أحد أهم الوسائل المستعملة في استقصاء الكبد والطرق الصفراوية, إذ إنه وسيلة آمنة، غير راضة، يمكن تكراره بسهولة مع بقاء المريض على الريق دون الحاجة لأي تحضير دوائي. يمتاز التصوير الراجع للطرق الصفراوية عن التصوير بالأمواج فوق الصوتية بأنه وسيلة تشخيصية وعلاجية في آن واحد إلا أنه يتطلب وجود فريق طبي شعاعي متكامل. تشير دراسات الأدب الطبي اليوم لأهمية متزايدة [5] للـ Endoscopic ultra sonography ) Eus ) ودراسة الطرق الصفراوية بالرنين المغناطيسي (MRCP ),إن عدم وجود هذين الاستقصاءين في مشفانا أعطى للـ ERCP التشخيصي والعلاجي أهمية خاصة للبحث . This study has included /105/ patients admitted to the department of internal medicine at Al-Assad University Hospital. The goal of the study is to compare the conclusion of ultrasound of patients expected to have a lesion at bile ducts inside and outside the liver with those of Endoscopies retrograde cholangiopancreatography (ERCP). To ensure the role of (ERCP) in diagnosis and treatment, ultrasound is one of the most important methods used to study the liver and bile ducts because it is safe, noninvasive, and can easily be applied; also, sedation of the patient is not necessary. ERCP is more sensitive than ultrasound in that it can be used for both diagnosis and treatment, but it requires the efforts of both radiologists and internal doctors. Medical literature refers to the importance of (EUS) and MRCP for studying biliary ducts lesions. Since Al-Assad Hospital does not have the last two methods, we apply the ERCP.